2021
DOI: 10.3390/medicina57090931
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Is Related to Worse Clinical Outcomes of COVID-19

Abstract: Backgroundand Objectives: Aspirin is used globally to reduce pain and inflammation; however, its effect in patients with coronavirus disease (COVID-19) is not fully investigated and remains controversial. We evaluated the association between aspirin and COVID-19 outcomes using nationwide data from the Korean National Health Insurance System. Materials and Methods: This was a retrospective observational cohort study that included 22,660 eligible patients who underwent COVID-19 testing in South Korea between 1 J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…After screening on titles, abstracts and full texts, forty comparative studies involving 4867,795 individuals were included in this review, in which eight are from the United States of America (USA), six are from South Korea, and four are from the United Kingdom (UK) ( Figure 1 ). 10 , 11 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 Twenty-eight (70%) of the included studies enrolled patients positive to SARS-CoV-2 tests. All forty studies included only adult cases.…”
Section: Resultsmentioning
confidence: 99%
“…After screening on titles, abstracts and full texts, forty comparative studies involving 4867,795 individuals were included in this review, in which eight are from the United States of America (USA), six are from South Korea, and four are from the United Kingdom (UK) ( Figure 1 ). 10 , 11 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 Twenty-eight (70%) of the included studies enrolled patients positive to SARS-CoV-2 tests. All forty studies included only adult cases.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, several studies on the administration of ASA in COVID-19 patients show a variable picture on the outcome [38,39,[48][49][50][51][52][53][54]. On the one hand, an improvement in mechanical ventilation and in-hospital deaths [38], and on the other hand, no effect of ASA on mortality [39,48,50,51,53,54] were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, they found that a positive chest CT was correlated with antiplatelet intake despite adjustment (OR = 12.1 (1.41–167), p = 0.0354). While another retrospective cohort showed an increased risk of oxygen therapy in patients prescribed aspirin within 2 weeks after diagnosis ( Kim et al, 2021 ); but here propensity matching failed to adjust for a history of CAD. SARS-Cov-2 was indeed found to infect pulmonary endothelial cells causing endothelial injury and thrombosis ( Acosta and Singer, 2020 ).…”
Section: Aspirin and Covid-19mentioning
confidence: 91%